2008
DOI: 10.1007/s00213-008-1163-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 50- and 100-g l-tryptophan depletion and loading formulations for altering 5-HT synthesis: pharmacokinetics, side effects, and mood states

Abstract: There are important considerations when choosing among formulation sizes for use in Trp manipulation studies, and the complete 7-h time-course data set of the typical plasma Trp measures presented here may help researchers decide which methodology best suits their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 54 publications
6
74
1
Order By: Relevance
“…As in previous studies (Dougherty et al, 2007; Dougherty et al, 2008b; Dougherty et al, 2010), both formulations included: L-alanine 2.75 g; L-arginine 2.45 g; L-cysteine 1.35 g; Glycine 1.60 g; L-histidine 1.6 g; L-isoleucine 4.00 g; L-leucine 6.75 g; L-lysine HCl 4.45 g; L-methionine 1.5 g; L-phenylalanine 2.85 g; L-proline 6.10 g; L-serine 3.45 g; L-threonine 3.25 g; L-tyrosine 3.45 g; and L-valine 4.55 g. The tryptophan-balanced control mixture included 5.15 g of L-tryptophan. To increase palatability, these formulations were mixed with 1 g saccharin, 2.5 g of sugar-free powdered fruit drink mix, and 0.2 L of chilled filtered water, and L-cysteine and L-methionine were administered in gelatin capsules.…”
Section: Methodssupporting
confidence: 53%
“…As in previous studies (Dougherty et al, 2007; Dougherty et al, 2008b; Dougherty et al, 2010), both formulations included: L-alanine 2.75 g; L-arginine 2.45 g; L-cysteine 1.35 g; Glycine 1.60 g; L-histidine 1.6 g; L-isoleucine 4.00 g; L-leucine 6.75 g; L-lysine HCl 4.45 g; L-methionine 1.5 g; L-phenylalanine 2.85 g; L-proline 6.10 g; L-serine 3.45 g; L-threonine 3.25 g; L-tyrosine 3.45 g; and L-valine 4.55 g. The tryptophan-balanced control mixture included 5.15 g of L-tryptophan. To increase palatability, these formulations were mixed with 1 g saccharin, 2.5 g of sugar-free powdered fruit drink mix, and 0.2 L of chilled filtered water, and L-cysteine and L-methionine were administered in gelatin capsules.…”
Section: Methodssupporting
confidence: 53%
“…My colleagues and I 89 found that 25 g, 50 g, 75 g and 100 g mixtures reduced human plasma tryptophan by 42%, 60%, 65% and 64%, respectively. Dougherty and colleagues 90 also found a more robust depletion with a 100 g mixture than a 50 g mixture. However, the 2 mixtures caused similar lowing of mood -the 100 g mixture caused greater attrition -even though ratings of somatic symptoms were similar in the 2 groups.…”
Section: Theory and Practice In Depleting Tryptophan: What Is The Besmentioning
confidence: 91%
“…5-hydroxyindolacetic acid is a metabolite of serotonin which reflects central nervous system serotonin turnover [28]. On the other hand, a decrease in Trp availability can lead to a substantial lowering of serotonin synthesis and turnover [29][30][31]. Therefore, neuronal serotonin synthesis is strictly linked to Trp availability in cerebrospinal fluid [32], which depends in turn on plasma Trp/LNAA ratio, as already mentioned above [17,18].…”
Section: Aromatic Amino Acids: Biochemical and Nutritional Aspectsmentioning
confidence: 90%
“…Trpfree drinks cause a rise in total plasma amino acid concentration, which in turn induces protein synthesis. Available plasma free-Trp is incorporated into new synthesized proteins and as a consequence its level in blood and tissues falls [31,43]. At the same time, brain Trp uptake is reduced and serotonin synthesis is downmodulated [32].…”
Section: Altered Intake Of Aromatic Amino Ac-ids and Psychoactive Effmentioning
confidence: 99%
See 1 more Smart Citation